PELATIHAN PEMBUATAN AQUASCAPE UNTUK KELOMPOK ENTERPRENEUR PEMUDA KARANG TARUNA/PELAJAR : Training Aquascape Product For Entrepreneur Groups Youth Clubs/Students - Yunandar Yunandar; Dini Sofarini; Suhaili Asmawi; Rina Nur Hidayah; Recza Julianor; Jonathan Cahyono (Universitas Mataram, 2023)
Aquascape is a miniature aquatic ecosystem. The interaction between abiotic components with fish and plants creates an aesthetically pleasing underwater scene. Waters are fish habitats that directly affect the health and development of fish. The increasing turbidity of the waters from the water source and the increase in feed residues and waste metabolites decrease the quality of water and the beauty of the aquascape. Turbidity and ammonia levels exceeding Environmental Quality Standards lead to hypoxia and provoke disease growth. This service activity aims to improve water quality, especially turbidity parameters, to support ornamental fish activities through the concept and design of an optimal aquascape unit, with the addition of aquatic plants as one of the filter media. Methods of activities consists of surveys, socialization, coaching, manufacturing practices, and maintenance of units. Aquascape design for ornamental fish farming is a product of this activity. The implementation of activities from May to July 2023, in Cempaka Village, Cempaka District, Banjarbaru City at Groups Youth Clubs. Training on design and aquascape unit biofiltration system with success of 75%. The practice of installing aquascape media is 80%. The evaluation indicator of the knowledge improvement component of the partner group is 80%. Unit operational and maintenance techniques, knowledge of biota selection, and feeding schedule increased by 70%. The partner's commitment to jointly manage and run aquascape activities is social capital, in addition to increasing the contribution to partner income. Reusing water through a filter unit can make the aquascape system more efficient. This filtering mechanism neutralises ammonia compounds and other toxic substances before entering the aquascape ecosystem. Aquascape techniques can streamline the cost of water change, maintenance, and aeration. Reducing harmful substances from the excess of feed, feces as well as lowering turbidity.